Families Raising Disabled Children - McLaughlin, J. author. aut Link
XIII, 228 p.
Keywords: Drawing upon qualitative material from parents and professionals, including ethnography, narrative inquiry, interviews and focus groups, this book brings together feminist and critical disability studies theories.